Spectrophotometric Determination of Citalopram in Pharmaceuticals Using Folin-Ciocalteu Reagent - Raza, Asad; Mahmood Ansari, Tariq (Asian Journal of Chemistry, 2013)
A simple and selective spectrophotometric method for the determination of citalopram hydrobromide is described. The method is based on the formation of blue coloured chromogen due to reduction of tungstate in Folin-Ciocalteu reagent by citalopram in alkaline medium. The coloured species has an absorption maximum at 730 nm and the Beer's law obeys over the concentration range of 5-75 μg mL-1. The limit of detection and quantification value are 3.43 and 11.34 μg mL-1 respectively. Application of the proposed method to bulk powder and commercial pharmaceutical tablets is also presented. No significant difference was obtained between the results of the proposed method and the official USP method. The procedure described in this paper is simple, rapid and extraction free.